Draft Analysis ROV (Remotely Operated Vehicle) Exploration For Underwater - Firmansyah M A; Vandika A Y (Bandar Lampung University (UBL), 2017)
Indonesia is one country that has greatest.Sea waters is an ecosystem rich with natural resources that can be utilized for prosperity and well-being person.As it is known that 70% of the earth's surface covered olehwaters / sea and more than 90% of the biomass of life on the planet live in the sea. There for the ocean is an important part of human survival. (Sudrajad, 2006). Most of the territory of the Republic of Indonesia consists of ocean waters is located very strategically. Indonesian marine waters other than utilized as local and international communications facilities, also has a very rich marinere sources and other resources important among fisheries, coral reefs, mangroves, minerals, and its coastal area can be used as a tourist attraction which is underwater has interesting.Robot became one of the effective means to support human beings in terms of underwater exploration. Because humans have limitations to be able to withstand the pressure underwater so great. Underwater robots have become one of the effective means to replace humans in exploring underwater. Exploration in this case has a broad meaning, ranging from the simple exploration of the underwater ecosystem sort ofobservation, to discover such high risk seabed sampling to detect metal mine at a depth of more than 1000m. Such exploration can still be done without the need for direct human intervention in exploring.By using underwater robots, humans are just waiting on the mainland for the next task is done by venturing underwater robot.